2009
DOI: 10.1016/j.cplett.2008.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Second-order quadrupolar shifts as an NMR probe of fast molecular-scale dynamics in solids

Abstract: Molecular-scale dynamics on the nanosecond timescale or faster can have a measureable influence on isotropic NMR frequencies of quadrupolar nuclei. Although previously studied in solution, where it is usually referred to as the "dynamic shift", this effect is less well known in solids. Here we demonstrate that multiple-quantum NMR measurements of isotropic quadrupolar shifts are a simple way to probe nanosecond timescale motions in solids. We measure the 11 B (spin I = 3/2) shifts of the resolved boron sites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…In summary, the NMR study of quadrupolar nuclei provides powerful tools for characterization of dynamics within solid materials, but it is more common to see studies that take advantage of the direct measurement of residual quadrupolar than resonance’s line width. , In this case, we showed that there is a dynamical effect that appears in the 27 Al resonances of LDH materials and that this effect is counteranion dependent. Since understanding dynamics within LDH materials seems to rise as a crucial problem, and given the fact that 27 Al nuclei are located at the heart of the mineral layers and yet are sensitive to dynamics within the interlayer space, we think that this phenomenon needs to be advertised, as its understanding will eventually provide the scientific community with a universal tool for future studies in this domain.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In summary, the NMR study of quadrupolar nuclei provides powerful tools for characterization of dynamics within solid materials, but it is more common to see studies that take advantage of the direct measurement of residual quadrupolar than resonance’s line width. , In this case, we showed that there is a dynamical effect that appears in the 27 Al resonances of LDH materials and that this effect is counteranion dependent. Since understanding dynamics within LDH materials seems to rise as a crucial problem, and given the fact that 27 Al nuclei are located at the heart of the mineral layers and yet are sensitive to dynamics within the interlayer space, we think that this phenomenon needs to be advertised, as its understanding will eventually provide the scientific community with a universal tool for future studies in this domain.…”
Section: Discussionmentioning
confidence: 71%
“…Studies include nitrate, chloride and carbonate ions in related Li 2 Al and Mg 3 Al-LDH. The presence of 27 Al nuclei in LDH materials makes them an easy target for NMR studies thanks to 27 Al’s high sensitivity in NMR. The NMR of quadrupolar nuclei has many features that make it suitable for dynamical and structural studies. For instance, measuring first- or second-order quadrupolar interactions can give crucial information on the nuclei’s chemical environment and dynamical behavior. NMR studies on LDHs have shown that as the electric charge density of the mineral layer decreases, there is a broader distribution of 27 Al environment ,, and that this distribution also has an effect on the inhomogeneous line width of the 27 Al solid-state NMR resonances, but so far, nothing has been investigated on the effects of dynamics on 27 Al spectra. It is possible to study the homogeneous line broadening induced by first-order quadrupolar interaction fluctuation on satellite transitions (STs) to investigate local dynamics on quadrupolar nuclei. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Variable-temperature 1 H-decoupled 11 B MQMAS NMR spectra of o- , m -, and p -carborane were obtained using the method described in Figure 1a of ref ; the three-pulse “sandwich” was found to be most generally effective for excitation of triple-quantum coherence because of the small magnitude of the residual quadrupolar splittings. 1 H decoupling was used, with a field strength of 50 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…В первое время ди-намические сдвиги наблюдались только в ЭПР-спектрах. Позднее, благодаря применению сильных квантующих полей в ЯМР-спектрометрах, стало возможным наблю-дение динамического сдвига спектров ЯМР для вязких жидкостей, обладающих большим временем корреляции атомного движения [14][15][16][17][18], и для твердых тел с высокой атомной подвижностью [19].…”
Section: Introductionunclassified